2021
DOI: 10.1109/jssc.2020.3046484
|View full text |Cite
|
Sign up to set email alerts
|

Four-Channel Differential Lock-in Amplifiers With Autobalancing Network for Stimulated Raman Spectroscopy

Abstract: We introduce a multi-channel integrated circuit for fast Stimulated Raman Scattering (SRS) microscopy on multiple simultaneous frequencies at a frame rate higher than 1 frame/s. The chip is a 4-channel differential readout system, based on the lock-in technique. It is able to measure down to 10 ppm SRS signal, over a wide range of input optical powers (50 μW -600 μW per channel), with a pixel dwell time of only 30 μs. Each acquisition channel includes 2 low-noise preamplifiers, 2 variablegain amplifiers, a ful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…This protocol has three minor limitations. First, the detection scheme employed in this contribution consists of a nonconventional, multichannel lock-in detector designed and built in-house by Sciortino et al 26 As demonstrated previously 25 , this detector can be replaced by an off-the-shelf system complexity and lead to losses of optical power and pulse broadening.…”
Section: Representative Resultsmentioning
confidence: 99%
“…This protocol has three minor limitations. First, the detection scheme employed in this contribution consists of a nonconventional, multichannel lock-in detector designed and built in-house by Sciortino et al 26 As demonstrated previously 25 , this detector can be replaced by an off-the-shelf system complexity and lead to losses of optical power and pulse broadening.…”
Section: Representative Resultsmentioning
confidence: 99%
“…ANN algorithms are inspired by the human brain and nervous system. ANNs can learn the interrelationships between water environment variables and water quality indicators, using interconnections and 'new' variable values to be able to quantitatively predict changes in water environment quality [5][6].…”
Section: Problems In the Studymentioning
confidence: 99%
“…In 2021, Sciortino et al [23] summarised and collated the effect of fibre material on the non-linear effect, stating that the SRS power can be expressed as…”
Section: Materials Componentsmentioning
confidence: 99%